دور تطبيق مبادئ إدارة الجودة الشاملة في تدنية تكاليف المؤسسات الاقتصادية - حمدية، سعاد; بن عيشي، عمار (University of Eloued جامعة الوادي, 2025)
This study aims to study the role of applying Total Quality Management (TQM) principles in reducing costs in economic institutions. To achieve the objectives of the study, the descriptive-analytical method was adopted, and a questionnaire was used as a tool for data collection. The questionnaire was distributed to a random sample consisting of (a manager, a deputy manager, and department heads) in the economic institutions under study (Biskra Textile and Equipment Company, Naftal Biskra District, Biskra Cable Manufacturing Company, and the Grand Mills of the South Biskra), with a total of (40) individuals. To analyze the data and test the study’s hypotheses, the statistical program (SPSS) was used. This study concluded that the level of application of Total Quality Management (TQM) principles, represented in (support and commitment of top management, customer focus, employee participation and teamwork, continuous improvement, and relationships with suppliers), in the institutions under study was high, and it seek to reduce their costs, the study conclouded also that there is a statistically significant relationship between the application of TQM principles and cost reduction in the institutions under study.
The Role of Applying Total Quality Management (TQM) Principles in Reducing Costs of Economic Institutions A Study of a Sample of Economic Institutions in Biskra Province
مقال
Keywords: إدارة الجودة الشاملة; مبادئ إدارة الجودة الشاملة; تدنية التكاليف; Total Quality Management; TQM Principles; Cost Reduction